Fluoroquinolones Inhibit, while β-Lactams Fail Against Biofilm-Producing Bacteria Isolated from Paediatric Syrups - Deborah Damilola Yusuf; Ejiro Dowe (Molecular and Cellular Biomedical Sciences, 2026)
Background: Paediatric syrups are sugar-rich solutions widely preferred in paediatric healthcare due to their palatability, although they are highly prone to microbial contamination. Of particular concern is the presence of biofilm-producing microorganisms; existing studies have focused on contamination while overlooking the enhanced resistance mechanisms conferred by biofilm formation. This study aimed to determine the antibiogram profile of bacterial isolates from commonly prescribed paediatric syrups administered by caregivers to patients at selected healthcare centers.Materials and Methods: A total of 392 syrup sample swabs were collected from hospitals and community sources. Bacterial isolation and identification were performed using standard microbiological methods. Biofilm production was evaluated using the test-tube method, and antibiotic susceptibility was determined via the disk diffusion method.Results: Bacterial counts ranged from 3.0±2.0×10³ to 10.7±3.05×10³ CFU/mL, with community samples showing the highest counts. Bacterial isolates identified included Proteus vulgaris, with the highest frequency of occurrence (18.75%) > Streptococcus agalactiae, Klebsiella pneumoniae, Acinetobacter baumannii (12.59%) > Pseudomonas aeruginosa, Arthrobacter agilis, Enterococcus faecium, Enterobacter cloacae, Escherichia coli (6.25%). All isolates produced biofilms significantly different (p<0.05) from the negative control (broth tube without bacterial cells), except Arthrobacter agilis. Antibiotic susceptibility testing indicated multidrug resistance, particularly against amoxicillin and amoxicillin-clavulanate, while showing comparatively higher susceptibility to fluoroquinolones.Conclusion: P. vulgaris was the most frequent isolate, while K. pneumoniae and A. baumannii produced the strongest biofilms. The highest resistance was observed against amoxicillin and amoxicillin-clavulanic acid, whereas fluoroquinolones remained the most effective. Paediatric syrups can harbor biofilm-producing multidrug-resistant bacteria, underscoring the importance of monitoring and safe handling.Keywords: paediatric syrup, antibiogram profile, biofilm, bacterial isolates, test-tube method